An Empirical Study of Goan Students’ Behaviour towards Advertisements - Costa, Juao C. (Indian Journal of Marketing, 2012)
Advertisements have two basic purposes: to inform and persuade. Advertiser’s primary mission is to reach the prospective customers and influence their awareness, attitude and buying behavior. They spend a lot of money to keep individuals interested in their products. To succeed, they need to understand what makes potential customers behave the way they do. The influencing factors may include advertisements, friends, parents, etc. The buying behavior and spending pattern of the students go hand in hand. Once they decide what to buy, they automatically decide how much to spend. When they decide what to buy - Advertisements, Friends, Parents and various other factors play a very important role. Prominent among them are the advertisements and friends. The present article deals with and tries to understand buying behavior and spending pattern of consumers vis-Ã -vis the influence of advertisements on the same. In order to collect the data, 2108 students from all over Goa were surveyed. The data was classified into - Gender (Male and Female), Location (Rural and Urban), Region (South and North Goa) and Education (SSCE, HSSCE, Graduates, and PG). Information on various areas such as TV at home, Watching advertisements, factors attracting them towards advertisements, time spent in front of the TV, spending pattern, consumption of harmful products, various vices, etc. was collected. The data so collected was cross tabulated and with the help of chi-square test was tested statistically. The analyses concluded that overall, advertisements do not influence the spending pattern and buying behavior of the students and thus, the hypothesis formed for the purpose was accepted.